Aplicabilidade do princípio da publicidade nas licitações públicas - Sant'Anna, Marília Mendonça Morais (2008)
It is the importance of the plea and explanation, the very idea of public administration, the principle of advertising that appears next to the other as the legality, morality and impersonality, as provided for in art. 37 of the Federal Constitution of 1988, all constitutional Guiding principles of administrative action. Given the multiplicity of concepts and conceptions of the term advertising, it is initiated by defining it and delimit it, and therefore uses, as a support, the comparison in the face of other institutions, such as propaganda, notification and communication. Given that the question of the study was: if the existence of the Constitutional Principle of Advertising as its applicability gives us licitatórios processes? Taking as general objective of the show exactly the importance of applying this principle in the bidding, since the act convocatório to its finalization and how is key in a Democratic State of Law. The method of approach was the deductive and the technique was used to search indirect documentary: law and literature and teaching. It, therefore, advertising, pass key in the fight for visibility of the shares of Public Administration. In that sense, linking itself to other constitutional principles, such as morality, legality and impersonality, the principle of publicity imposes administrative standards of conduct, which are subject all players who Speak and decide on behalf of the state